The Refusal Speech Act in "Me Before You" Movie - Rianda Anggraini; Ambalegin Ambalegin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This study aimed at identifying the strategies in refusal in Me Before You. This movie was adapted by the novel and the writer’s name is Jojo Moyes. Refusal has two types, they are indirect and direct refusal. Indirect refusal is mostly used because it can decrease the negative effect (FTA) of refusal itself. The strategies of indirect refusal are found alternative, reason and explanation, request for aditional information, apology or regret, repetition of part previous discourse, and posponement. The study applied an observational method and non-participatory technique by Sudaryanto. Then, this study applied pragmatics method to analyze the data. The finding showed that there were 5 utterances that contained request for additional information and this strategy was mostly used by the characters in this movie.